SGLT2 inhibitors as add on therapy in type 2 diabetes: a real world study - Tamez Pérez, Héctor Eloy; Delgadillo Esteban, Enrique; Soni Duque, David; Hernández Coria, Mayra Ivonne; Tamez Peña, Alejandra Lorena (2017)
Abstract Background: Type 2 diabetes mellitus (T2DM) is a progressive chronic disease associated with severe microvascular and macrovascular complications. Our aim is to assess the real world effectiveness of SGT" inhibitors in achieving metabolic therapeutic goals. Methods: A retrospective, observational study. Inclusion criteria for patients were a previous diagnosis of type 2 diabetes mellitus, age > 18 years, patients receiving either dapagliflozin 10 mg and/or canagliflozin 300 mg. We excluded pregnant patients, patients with type 1 diabetes mellitus and acute metabolic complications of diabetes. Patients included in the analysis were enrolled in a health plan at least 6 months prior to the index date (baseline period) and in the 6 months following the index date (follow-up period). Achievement of glycated hemoglobin goals were established as <7%. Results: We screened 2870 Mexican patients; 288 (10.03% received SGLT2 inhibitors). Mean age for both groups of patients was 57.68±11.06 years. The dapagliflozin control rate was 19.56% and the canagliflozin control rate 18.96%. Monotherapy with SGLT2 inhibitors was used in 21 patients (6.25%). Overall HbA1c goals were met in 56 patients (19. 44%) with similar results with dapagliflozin or canagliflozin. The combination of SGLT2 inhibitors and sulfonylureas had the highest control rate (30.30%) compared to other regimens. Monotherapy was present in 6.25%. Insulin requirement was associated with poor control (2.8% vs. 18.05%, P<0.05, 95% CI [0.07, 0.84]). Combination therapy with DPP4 inhibitors was associated with better control (P<0.05, 95% CI, [1.10, 3.92]). Conclusion: No difference between the drugs was observed. Real-world effectiveness data of SGLT2 inhibitors show that the percentage of patients reaching metabolic goals is low. SLGT2 inhibitors were used more frequently as combined therapy. Keywords: Dapagliflozin, Canagliflozin, Diabetes Mellitus, Type 2, Effectiveness research, comparative, Hemoglobin A, Glycosylated